Data Analysis of Occupational Health and Safety Management and Total Quality Management Systems - Ahmet Yakut; Yrd. Doç. Dr. Rıfat Akbıyıklı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2013)

(untitled)
In our study, Total Quality Management, Occupational Health and Safety on the effects of the construction industry, building sites of Istanbul evaluated with the results of the survey of 25 firms. For Occupational Health and Safety program, walked healthy, active employees in her role increased and will increase the importance of education. Due to non-implementation of the OHS system in our country enough, work-related accidents and deaths and injuries resulting from these accidents is very high. Firms as a result of the analysis, an effective health and safety management system needs to be able to fulfill their responsibilities. This system is designated as OHSAS 18001 Occupational Health and Safety Management System and the construction industry can be regarded as the imperatives.